Shark's tooth: oxford literacy web - Moon, Nicola; McPhillips, Robert (Oxford University Press China, 1999)
Guides pupils through the skills associated with learning to read and write with literary styles within the genres of fiction, non-fiction, rhymes, language, and poetry. This work includes illustrations that combine to ensure diversity and enjoyment, and stories that extend vocabulary. They are available in standard and 'big book' format.